Covid-19 Pandemic: Adaptability of Vocational School Strategic Planning - Munir, Khoirul; Basrowi, Basrowi; Suseno, Bambang Dwi (LPPM Universitas Bina Bangsa, 2022)
This research aims to test the adaptability of vocational school strategic planning in the face of the Covid 19 Pandemic. Along with important aspects of how to adjust in the era of Industry 4.0. This preparation is in the form of a Strategic Plan guided by SWOT analysis and valuable to vocational schools. This study uses quantitative research methodology and then combined with a descriptive qualitative approach. Data collection is used non-probality sampling with Google Forms and questionnaire devices. A random sample of 30 people was selected as a sample. The school has 15 internal students and 15 external students. The overall index of vocational schools in Cikande District of Serang Regency produced the following findings. The strength is 8.42 points, the Weakness is 5.98 points, the Odds are 8.62 points, and the Threat is 6.70 points. When calculated, the coordinate point of internal analysis worth 2.26 (X) and the coordinate point of external analysis worth 1.92 (Y) are obtained (Y). It was determined that vocational schools in Cikande Sub district were in a position to be classified as Aggressive or Prima in quadrant 1